An energy-based pedestrian accessibility indicator - Sousa, Nuno (2017)
Conclusions: the methodology proposed here shows that for the hilly city of Coimbra, Portugal, centrality, more than relief, is the chief factor determining a location’s pedestrian accessibility. This methodology, based on classic definitions of accessibility as disutility and using on human effort (as measured by muscular energy spent to walk the streets network) as impedance, is general and can be applied to any city. Since human effort rises considerably with slope, it especially adequate to hilly cities.